NAFKAH MADHIYAH ANAK PASCA PERCERAIAN: STUDI KOMPARATIF HUKUM PERDATA DAN HUKUM ISLAM DI INDONESIA - Yudha Sri Wulandari (The Juris, 2026)
This study examines the normative construction of post-divorce child maintenance in two legal systems that apply in Indonesia, namely civil law (KUHPerdata) applied by the District Court and Islamic law (Compilation of Islamic Law) applied by the Religious Court. The method used is a comparative juridical-normative approach with a legislative, conceptual, comparative law, and case approach to the 2020–2024 verdict. The results of the study show two findings. First, both legal systems place child support obligations as an inherent obligation on parents, especially fathers, and are not erased by divorce (Pasal 298 KUHPerdata; Pasal 156 huruf d KHI; Pasal 41 UU Perkawinan). Second, the difference lies in the theoretical doctrine, namely civil law constructs it as an inherent and reciprocal alimentatieplicht, while Islamic law discusses it through the doctrine of lil-intifa' versus lit-tamlik which had been the basis for the rejection of the lawsuit in the Decision MA No. 608 K/AG/2003, before being reconstructed through SEMA No. 2 Tahun 2019.